Newtons method for nonlinear stochastic wave equations driven by one-dimensional Brownian motion - Henryk Leszczyński; Monika Wrzosek (Mathematical Biosciences and Engineering)
We consider nonlinear stochastic wave equations driven by one-dimensional white noise with respect to time. The existence of solutions is proved by means of Picard iterations. Next we apply Newton's method. Moreover, a second-order convergence in a probabilistic sense is demonstrated.